Mongolia National Low Emission Stove Strategy : Completing the Transition to a Sustainable Market for Cleaner Stoves - World Bank Group (World Bank, Washington, DC, 2015)
Building on six years of technical assistance, policy dialogue and recent stove switching program experience in Ulaanbaatar, this report sets out a proposed national low-emission stove strategy for Mongolia. The objective of the strategy is to establish a sustainable market for low emission stoves in Mongolia. The report focuses on clean heating and cooking stoves as well as small water heating boilers used in peri-urban ger areas of Ulaanbaatar and other Aimags and Soum centers.